Age and growth of the smooth hammerhead shark, Sphyrna zygaena, in the Eastern Equatorial Atlantic Ocean, using vertebral sections - Coelho, Rui (2017)
The smooth hammerhead shark Sphyrna zygaena (Sphyrnidae) is regularly caught as bycatch in pelagic longline fisheries, but is one of the least studied of all pelagic sharks. Recently, ICCAT (International Commission for the Conservation of Atlantic Tunas) issued recommendations underlining the need for more studies on the life history parameters of this and other pelagic shark species. To this end, the age and growth of S. zygaena were studied in the Eastern Equatorial Atlantic Ocean, in an area where growth parameters were not yet available for this species. Data from 139 specimens, caught between June and September 2009, ranging in size from 136 to 233 cm fork length (FL), were analysed. Preliminary trials were carried out to assess the most efficient growth band enhancement technique. These indicated that sectioning the vertebrae into 500 μm sections followed by staining with crystal violet produced the best results. Growth models were fitted using the traditional von Bertalanffy growth equation and a modification of this equation using a known size at birth. Growth models were compared using the Akaike information criterion (AIC). The von Bertalanffy growth equation seemed to be the most adequate model to describe growth in this species, with resulting growth parameters of L inf = 272 cm FL, k = 0.06 year for males and L inf = 285 cm FL, k = 0.07 year for females. In the first four years of life, S. zygaena grows 25 cm per year on average, but its growth slows down in later life. Future stock assessment models should incorporate these age and growth parameters for species management and conservation.